Medical Termination of Pregnancy in Queen - Sunil Parmar; Singh, Kiran; Biswas, Newton; Kumar, Sushil; Dwivedi, Poornima; Srivastava, Neeraj; Khan, Meraj Haider (Animal Reproduction Update, 2024)
Cats routinely undergo medical termination of pregnancy (MTP) to control reproduction by terminating unwanted pregnancies. Post-coital contraception, also known as emergency contraception or pregnancy termination, are indeed common procedures in veterinary practices for companion animals like bitches and queens. Typically, a veterinarian guides these procedures, which may involve medications or surgical interventions based on the pregnancy stage and specific circumstances. Pet owners must discuss their options with a veterinarian to determine the best course of action for their animal’s health and well-being, taking into account factors such as the dam’s age, health issues, or low breeding value offspring. Medical termination of pregnancy has more demand in feline practice due to the higher incidence of unwanted pregnancy for their feral nature. In such cases, termination of pregnancy may be achieved by using only one medicament or a combination of two or more medicaments. A combination of either natural or synthetic analogues of prostaglandin F2 and dopamine agonists or anti-progestins yielded good results in healthy bitches and queens with confirmed pregnancy. Regular sonographic examinations and vaginal discharge observation follow to confirm the loss of pregnancy. At certain times, blockage of two hormones, i.e., prolactin and progesterone, is used, which has high success rates for MTP in small animals. The benefits of combined administration include low doses with fewer side effects. Considering all such issues, this treatise deals with indications for MTP, symptoms to identify pregnancy, especially in feral cats, and the application of various protocols for successful results with uneventful outcomes.
Keywords: Abortion; Cabergoline; Cloprostenol; Medical termination of pregnancy-MTP